Kewenangan Pemerintah Daerah Dalam Penerbitan Persetujuan Bangunan Gedung Pasca Berlakunya Perppu Nomor 2 Tahun 2022 Tentang Cipta Kerja - Ari Wulandari (Fakultas Hukum Universitas Narotama, 2023)
The issuance of Government Regulation in Lieu of Law (Perpu) Number 2 Year 2022 on Job Creation has a significant impact on building permits in Indonesia. The Perpu aims to encourage the acceleration of building permits by reducing bureaucracy and improving efficiency in the approval process. However, although this regulation provides steps in changing building licensing regulations, there are limitations on the authority of local governments in issuing building approvals after the enactment of the regulation. Surabaya City Government's authority to issue PBG is through the Office of Investment and Integrated Stu Pintu (DPMPTSP) based on technical recommendations from the Office of Public Housing and Settlement Areas and Land (DPRKPP). In providing Building Permit services to the community, it needs to be supported by adequate financing. Local revenues, including Local Tax and Retribution (PDRD) revenues, as regulated in Law Number 1 Year 2022 on Financial Relations between the Central Government and Local Governments have regulated the types of retribution that can be collected by the Local Government when providing services to the community. The types of retribution that can be levied on the community include Building Construction Permit Retribution which is used for regional expenditure in the form of funding the implementation of government affairs that fall under regional authority. One of the mandatory affairs related to basic services, the implementation of building construction in regency/city areas, including the granting of Building Construction Permit, is one of the priorities in allocating regional expenditure. Local governments are authorized to collect IMB/PBG retribution, by first establishing a local regulation on retribution in accordance with the provisions of laws and regulations.Keywords: PBG, Authority, Local Revenue